1993
DOI: 10.1016/0014-5793(93)80376-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of protein kinase C isoforms and enzymic activity from the αT3‐1 gonadotroph‐derived cell line

Abstract: Western blots of olT3-1 cell extracts were immunostained with antibodies specific for various protein kinase C (PKC) isoforms. These revealed the presence of PKC types a, E and c, but j?, y, 6 and r] were not detected. The potency with which partially-purified cytosolic PKC from aT3-1 cells was activated by phorbol 12,13-dibutyrate (PDBu), mezerein and 1,2-dioctanoyl-sn-glycerol was assessed in the presence and absence of Ca". The inhibitors staurosporine, K252a, H7, GF109203X and Ro 31-8220 were tested on bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 40 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…We also found that the expression of keratinocyte differentiation markers (e.g., involucrin and filaggrin) is greatly decreased in the epidermis from aged wild-type (CD44+/+) mouse skin treated with a PKNγ inhibitor, Ro31-8220 [4547] in the presence of HA L treatment (Fig. 4C-c vs. Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…We also found that the expression of keratinocyte differentiation markers (e.g., involucrin and filaggrin) is greatly decreased in the epidermis from aged wild-type (CD44+/+) mouse skin treated with a PKNγ inhibitor, Ro31-8220 [4547] in the presence of HA L treatment (Fig. 4C-c vs. Fig.…”
Section: Resultsmentioning
confidence: 75%
“…4B-b and Table 4). In contrast, aged wild-type (CD44+/+) mice similarly treated with a PKNγ inhibitor, Ro31-8220 [4547] do not display noticeable changes in HA S -induced PCNA-positive cell numbers and subsequent changes in epidermal thickness (Fig. 4B-c and Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo, the selectivity of Ro-31-8220 and GF109203X was addressed in ␣T3-1 gonadotrophs expressing PKC␣, -⑀, and -. In that study, Ro-31-8220 was shown to be a selective inhibitor of calcium-, diterpine-, and phorbol ester-activable PKC isozymes ␣ and ⑀, while GF109203X was an equally effective inhibitor of basal PKC activity composed of ␣, ⑀, and activity as of activated PKC activity (34). Other studies have addressed the selectivity of staurosporine and its analogs to inhibit soluble PKC and membrane-associated PKC.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether PKC is involved in this effect of EGF, we used two PKC inhibitors, Ro318220 and Gö6983, which have been shown to inhibit differentially novel and atypical PKCs, namely ⑀ and isoforms, respectively. The reported IC 50 of Gö6983 for PKC is 60 nM (17) and that of Ro318220 for PKC⑀ is 24 -48 nM (18,19), depending on the cell type studied. As shown in Fig.…”
Section: Effect Of Ro318220 and Gö6983 On The Ability Of Egf To Inhibmentioning
confidence: 99%